Pengembangan Media Pembelajaran Kartu Gambar Ilustrasi Berbasis Model Picture and Picture pada Materi Puisi Rakyat untuk Siswa SMP - Sari, Mimi Winda; Rukiyah, Siti; Murniviyanti, Liza (Lingua Susastra, 2024)
This research investigates the efficacy of the weak learning process in the development of illustrative picture card products utilizing the Picture and Picture learning model, specifically focusing on folk poetry content for seventh-grade students at SMP Negeri in Gelumbang. The research and development were conducted in accordance with the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The findings from the analysis indicate that the illustrative picture card product meets the material feasibility criteria with a score of 95%, the language feasibility criteria with a score of 93.7%, and the media feasibility criteria with a score of 97.5%. The aggregated validation across these three domains resulted in an overall percentage of 96.9%, signifying that the product is categorized as very valid and suitable for educational use. Furthermore, the illustrative picture card product concerning folk poetry material received a highly favorable response from users, achieving a percentage of 88.6% in the very practical category. Based on these outcomes, it can be concluded that the products developed by the researchers are classified as both valid and practical, thereby rendering them appropriate for integration into the learning process.